Life Time Performance Characterization of Solid Oxide Electrolysis Cells for Hydrogen Production. (2nd June 2015) - Sun, Xiufu; Chen, Ming; Liu, Yi-Lin; Hendriksen, Peter Vang
Abstract : Solid oxide electrolysis cells (SOECs) offer a promising technological solution for efficient energy conversion and production of hydrogen or syngas. The commercialization of the SOEC technology can be promoted if SOECs can be operated at high current density with stable performance over 5 years. In this work, long-term durability of Ni/yttria stabilized zirconia (YSZ) supported planar SOECs was investigated at 800 o C for electrolysis of steam at different current densities from 0 to -1.25 A/cm 2 . The SOEC cells are able to be operated at current density up to -1 A/cm 2, with a predicted life time of 2 - 3 years (continuous operation, setting 1.5 V as the upper voltage defining "end of life"). The results provide technological input to future design of electrolysis plants for hydrogen production.